2018
DOI: 10.7326/m16-2094
|View full text |Cite
|
Sign up to set email alerts
|

Association of Viral Suppression With Lower AIDS-Defining and Non–AIDS-Defining Cancer Incidence in HIV-Infected Veterans

Abstract: National Cancer Institute and National Institute on Alcohol Abuse and Alcoholism of the National Institutes of Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 57 publications
(54 reference statements)
7
46
1
5
Order By: Relevance
“…Keywords: Human immunodeficiency virus, Viral suppression, Sustained viral suppression, Durable viral suppression, Men who have sex with men Background Suppression of the human immunodeficiency virus (HIV) (< 200 copies/mL) among people living with HIV (PLHIV) is associated with immune reconstruction [1] and a decreased risk of acquired immune deficiency syndrome (AIDS)-defining conditions [2] and death [3]. In addition, viral suppression prevents the transmission of HIV to others [4].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…Keywords: Human immunodeficiency virus, Viral suppression, Sustained viral suppression, Durable viral suppression, Men who have sex with men Background Suppression of the human immunodeficiency virus (HIV) (< 200 copies/mL) among people living with HIV (PLHIV) is associated with immune reconstruction [1] and a decreased risk of acquired immune deficiency syndrome (AIDS)-defining conditions [2] and death [3]. In addition, viral suppression prevents the transmission of HIV to others [4].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…HCC diagnoses were determined from the VA national cancer registry by topography code C22.0 (liver) and morphology codes 8170-8180 (HCC) from the International Classification of Diseases for Oncology, Third Edition (ICD-O-3), 18 consistent with Surveillance, Epidemiology, and End Results coding algorithms. 19 The VA cancer registry records cancers diagnosed and/or treated within the VA. 7 ICD-O-3 codes validly identify cancer diagnoses, including HCC. 20 To account for lags in reporting diagnoses in the cancer registry and minimize the likelihood of missing HCC events, we supplemented HCC case finding with ICD-9 diagnoses for HCC (155.0, 155.1, and 155.2) recorded in the VA electronic medical record.…”
Section: Main Study Outcomesmentioning
confidence: 99%
“…3 Despite the rising incidence of HCC among HIV-infected individuals, the determinants of this malignancy remain largely unknown in this group. 4 Three prior studies found no association between HIV suppression and risk of HCC, [5][6][7] but these studies did not evaluate the effects of longer durations or higher levels of HIV viremia, nor did they account for cirrhosis. Moreover, previous studies among predominantly HIV/HCV-coinfected patients reported that lower absolute CD4+ cell counts increased the risk of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Dr. Justice and her colleagues analyzed cancer risk among HIV‐positive patients who had not yet achieved any viral suppression or who had achieved early or long‐term suppression . For AIDS‐defining cancers and non‐AIDS‐defining cancers associated with oncogenic viruses, the study revealed a similar stair‐step progression of increasing risk: HIV‐negative volunteers were at the bottom, followed by patients with long‐term viral suppression and then those early into their course of viral suppression.…”
Section: “Smoldering” Inflammation and Immune Activation?mentioning
confidence: 99%